Estetika Sejarah Desa Jimbaran Dalam Sajian Film Eksperimental - Mahardika, I Wayan Agus; Suardina, I Nyoman; Udayana3, Anak Agung Gde Bagus (Jurnal Ilmiah Wahana Pendidikan, 2023)
The story of Sri Dalem Batu Putih and Sri Dalem Batu Ireng told the history of the formation of Jimbaran Village. This story was presented in the form of an experimental film. The purpose of making this film was to introduce a new nuanced film by bringing elements of local culture and history of an area to the public. This work used the concept of an experimental film so that it could stimulate the minds of the audience and easily understand the flow and meaning conveyed from the historical film of Jimbaran Village. It used experimental theory from Himawan Prasista. The production used the method of pre-production, production and post-production creation. The film was supported by videographic composition techniques, two-dimensional animation, conventional shooting with cameras and aerial shots (shooting with drones). The visual presentation is also supported by the selection of gold and green as the dominant colors in the animation section. The gold color symbolized the wiser character, while the green color symbolized grandeur and prosperity that balanced emotions and tranquility which contained in the historical story of Jimbaran Village